Effect of Probiotic Supplementation on Cognitive Function and Metabolic Status in Alzheimer's Disease: A Randomized, Double-Blind and Controlled Trial - Akbari, Elmira; Asemi, Zatollah; Daneshvar Kakhaki, Reza; Bahmani, Fereshteh; Kouchaki, Ebrahim; Tamtaji, Omid Reza; Hamidi, Gholam Ali; Salami, Mahmoud (Frontiers in Aging Neuroscience, 2016)
Alzheimer's disease (AD) is associated with severe cognitive impairments as well as some metabolic defects. Scant studies in animal models indicate a link between probiotics and cognitive function. This randomized, double-blind and controlled clinical trial was conducted among 60 AD patients to assess the effects of probiotic supplementation on cognitive function and metabolic status. The patients were randomly divided into two groups (n=30 in each group) treating with either milk (control group) or a mixture of probiotic (probiotic group). The probiotic supplemented group took 200 ml/day probiotic milk containing Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium bifidum and Lactobacillus fermentum (2×109 CFU/g for each) for 12 weeks. Mini-mental state examination (MMSE) score was recorded in all subjects before and after the treatment. Pre- and post-treatment fasting blood samples were obtained to determine the related markers. After 12 weeks intervention, compared with the control group (-5.03%±3.00), the probiotic treated (+27.90%±8.07) patients showed a significant improvement in the MMSE score (P<0.001). In addition, changes in plasma malondialdehyde (-22.01%±4.84 vs. +2.67%±3.86 µmol/L, P<0.001), serum high-sensitivity C-reactive protein (-17.61%±3.70 vs. +45.26%±3.50 µg/mL, P<0.001), homeostasis model of assessment-estimated insulin resistance (+28.84%±13.34 vs.+76.95%±24.60, P=0.002), Beta cell function (+3.45%±10.91 vs. +75.62%±23.18, P=0.001), serum triglycerides (-20.29%±4.49 vs. -0.16%±5.24 mg/dL, P=0.003) and quantitative insulin sensitivity check index (-1.83±1.26 vs. -4.66±1.70, P=0.006) in the probiotic group were significantly varied compared to the control group. We found that the probiotic treatment had no considerable effect on other biomarkers of oxidative stress and inflammation, fasting plasma glucose and other lipid profiles. Overall, the current study demonstrated that probiotic consumption for 12 weeks positively affects cognitive function and some metabolic statuses in the AD patients.